Evaluation of the nutritional condition of school children in an endemic goiter zone - Solís Rosas, Cecilia (1989)
The nutritional condition of a school population of an endemic goiter region has been studied in order to elucidate whether the low ponderal indexes found might be related directly to the goiter or they are the consequence of other factors. A total of 3,517 children in school age between 6 and 17 years old, born and living in Urubamba-Cusco, Peru, an ancestral region of endemic goiler were examined. The nutritional condition was evaluated using the indexes heigh/age (H/A), weight/age (W/A) and weight/height (W/H). Both for the nutritional study as well as for the measurement of the goiter size the criteria recommended by the WHO/PAHO were utilized. Reference standards for the National Center Health Statistic (NCHS) were used to evaluate the nutritional condition. Using the index H/A 49% children presented retardation of height for their age, range 44% (Urubamba) to 64% (Maras). About 35% of the children had a lower weight for their age, range 20% (Urubamba) to 47% (Ollantaytambo). A low W/H index was found in 12% of the children, range 9% (Huayllabamba) to 21% (Chinchero). According to Waterloo's classification of undernourishment, 46% children had a chronic malnutrition, 7% acute malnutrition and 5% chronic-acute malnutrition. No correlation between the presence of goiter and chronic malnutrition was found which suggests that other factors aside from goiter are present to explain the malnutrition found in this school population (An Fac Med UNMSM II Epoca 1989; a (1-2): 27-30)